Sponge-like Modified White-Rot Fungi Adsorbent for Rapid Removal of Pb(II) and Cd(II) from Solution: Selective Performance and Mechanistic Insights - Chunxiao Wang; Zhirong Chen; Nana Wang; Jianqiao Wang; Runshen He; Yu Chen; Haerfosai Nuhu; Hang Chen; Zhixuan Lin; Minqi Fan; Mingdong Chang (Separations)
Heavy metal pollution, especially from Pb(II) and Cd(II), poses significant risks due to its persistence and bioaccumulation potential. Traditional removal methods face challenges like high costs and secondary pollution. This study developed a novel three-dimensional porous adsorbent XBS, derived from xanthate-modified Phanerochaete sordida YK-624 (a white-rot fungus), for the rapid and efficient removal of Pb(II) and Cd(II) from wastewater. Characterization showed that XBS has a sponge-like structure with abundant functional groups, significantly enhancing its adsorption capacity and kinetics. XBS achieved 96% Pb(II) and 32% Cd(II) removal within 1 min at a 0.25 g/L dose, reaching over 95% of the maximum adsorption capacity within 30 min for Pb(II) and 240 min for Cd(II). The maximum capacities were 224.72 mg/g for Pb(II) and 82.99 mg/g for Cd(II). Kinetic and thermodynamic analyses indicated a chemisorption-driven process, which was both endothermic and spontaneous. XBS exhibited high selectivity for Pb(II) over Cd(II) and other metals (Tl(I), Cu(II)), attributed to stronger covalent interactions with sulfur- and nitrogen-containing groups. Mechanistic analyses (XRD, FTIR, and XPS) revealed that removal occurs via ion exchange, complexation, and precipitation, forming stable compounds like PbS/CdS and PbCO3/CdCO3. Given its cost-effectiveness, scalability, and high efficiency, XBS represents a promising adsorbent for heavy metal remediation, particularly in Pb(II)-contaminated wastewater treatment applications.